412. Clinical and Pharmacoeconomic Evaluation of Antifungal Prophylaxis With Continuous Micafungin Compared to Posaconazole With Micafungin Bridging in Patients Undergoing Allogeneic Stem Cell Transplantation: A 6-Year Cohort Analysis. (26th November 2018) - Heimann, Sebastian M; Vehreschild, Maria J G T; Franke, Bernd; Cornely, Oliver; Hamprecht, Axel; Piepenbrock, Ellen; Scheid, Christoph; Vehreschild, Janne
Abstract: Background: Patients undergoing allogeneic stem-cell transplantation (aSCT) are at high risk of invasive fungal disease (IFD). Optimization of antifungal prophylaxis strategies may further improve patient outcomes and reduce treatment costs. Methods: We performed a retrospective single-center pharmacoeconomic evaluation comparing patients who received either posaconazole oral solution plus micafungin as intravenous bridging as required (POS-MIC) to patients who received only micafungin (MIC) as antifungal prophylaxis after aSCT at the University Hospital of Cologne. Epidemiological, clinical, and direct treatment cost data extracted from the Cologne Cohort of Neutropenic Patients (CoCoNut) were analyzed. Revised 2008 EORTC/MSG criteria were used for classification of IFD. Results: During the observation period from January 2010 to December 2015, 313 patients (97 patients in the POS-MIC and 216 patients in the MIC group) fulfilled inclusion criteria. Most patients were male ( n = 174; 56%) and median age was 52 years (range: 18–75 years). Acute myeloid leukemia was the most common underlying disease ( n = 146; 47%). In the POS-MIC and MIC group, median overall length of stay (LOS) was 42 days (IQR: 35–52 days) vs. 40 days (IQR: 35–49 days; P = 0.296), resulting in median overall direct treatment costs of €42, 964 (IQR: 35, 040 - €56, 348) vs. €43, 291 (IQR: €37, 281 vs. €51, 848; P = 0.993), respectively. In both groups, possible IFD occurred in six patients (6%) vs. 16 patients (7%; P = 0.696) and probable/proven IFD occurred in five patients (5%) vs. threepatients (1%; P = 0.051). Overall in-hospital mortality rates in the POS-MIC and MIC group were 10% ( n = 10) and 4% ( n = 9; P = 0.035). Kaplan–Meier analysis showed improved outcome of patients who received MIC at day 100 ( P = 0.037) and at day 365 ( P < 0.001) following aSCT. Multivariable cox-regression model demonstrated treatment on ICU as the most important independent covariate for mortality at day 100 (HR: 8.08; P < 0.001) and at day 365 (HR: 4.70; P < 0.001). Conclusion: We observed a higher mortality in patients receiving POS-MIC instead of MIC, which was not explained by breakthrough IFDs. The higher drug acquisition costs of micafungin compared with posaconazole oral solution did not translate into higher overall direct treatment costs. Disclosures: S. M. Heimann, Astellas: Grant Investigator and Lecture honoraria, Research grant and Speaker honorarium. M. J. G. T. Vehreschild, Astellas: Grant Investigator and Speaker's Bureau, Research grant. O. Cornely, Astellas: Consultant, Grant Investigator and Lecture honoraria, Consulting fee, Research grant and Speaker honorarium. J. Vehreschild, Astellas: Grant Investigator and Speaker's Bureau, Research grant and Speaker honorarium.